Age-Dependent D-dimer Cut-off to Avoid Unnecessary CT-Exams for Ruling-out Pulmonary Embolism - Altmann, M. M.; Wrede, C. E.; Peetz, D.; Höhne, M.; Stroszczynski, C.; Herold, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To evaluate the effect of an age-dependent D-Dimer cut-off in patients who underwent a computed tomography pulmonary angiogram (CTPA) for suspected pulmonary embolism (PE)Material and Methods: Retrospective application of an age-dependent D-dimer cut-off (age/100 in patients aged over 50) in 530 consecutive patients, both in- and outpatients, aged over 18, who underwent CTPA for suspected PE according to the guidelines.Results: The application of an age-dependent D-dimer cut-off showed a now negative test-result in 17 of 530 patients (3.2 %). The proportion was 4.1 % (17 of 418) in patients aged over 50. None of these 17 cases was diagnosed with PE in CTPA, the false-negative rate was 0 %. The effect could be seen in outpatients (14 of 377 [3.7 %]) as well as in inpatients(3 of 153 [2.0 %]) with no statistically significant difference (p > 0.05).Conclusion: The application of an age-dependent D-dimer cut-off as part of the guidline-based algorithm for suspected PE reduced the number of necessary CTPA in outpatients as well as in inpatients.Key points:• The application of an age-dependent D-dimer cut-off reduces the number of CTPA as part of the diagnostic algorithm in patients suspected for PENo reduction in diagnostic safety was found• The age adjustement performed equally in outpatients and inpatientsCitation Format:• Altmann MM, Wrede CE., Peetz D et al. Age-Dependent D-dimer Cut-off to Avoid Unnecessary CT-Exams for Ruling-out Pulmonary Embolism. Fortschr Röntgenstr 2015; 187: 795 – 800
Keywords: embolism/thrombosis; thorax; CT-angiography; vascular